A REVIEW OF THE EVENT INDUSTRY’S IMPACT AND CRISIS MANAGEMENT ANALYSIS DURING COVID-19 - Noor Zeti Aiqa Mad Isa; Eiren Sarah Emran; Nor Syahirah Azmi; Nur Afiqah Mohd Azan; Norlida Zakirai@Zakaria (International Journal of Accounting, Finance and Business, 2022)
This paper will review the impact of event’s industry and the crisis managementanalysis during COVID-19. The hospitality and event industry were the most affected sincegovernment of many countries’-imposed restriction of travelling by closing the borders to slowthe spread of the outbreak. This pandemic gives the greatest challenges to tourism and event’sindustry because this industry relies on a large group of people’s gathering. This paper willscrutinize the holistic impact of COVID-19 outbreak since world’s view this pandemic givethreat to human and livelihood after Second World War. Apart from that, this review also intentto highlight crisis management analysis undertake by event’s industry as a recovery process. Asearch of literature has been conducted through reputable electronic databases namely Scopus,ScienceDirect and ProQuest to search for the publish articles between year 2019-2022 in orderto analyse past research on the topics. Findings of the review indicated that, the impact ofpandemic affected event’s industry economically that incur lost to employment, organizationbankruptcy as well as disruption in supply chain. However, there is an opportunity arise tosustain the relevancy of event industry by emerging of technology to support virtual event. Thecrisis management analysis aids organization to oversee and forecast various planning to dealwith disaster in the future.